Presynaptic Cav2.1 calcium channels carrying a familial hemiplegic migraine mutation r192q allow faster recovery from syanptic depression in mouse calyx of held - González Inchauspe, Carlota María Fabiola (2012)
CaV2.1 Ca2+ channels have a dominant and specific role in initiating fast synaptic transmission at central excitatory synapses, through a close association between release sites and calcium sensors. Familial hemiplegic migraine type-1 (FHM-1) is an autosomal-dominant subtype of migraine with aura, caused by missense mutations in the CACNA1A gene that encodes the α1A pore-forming subunit of CaV2.1 channel. We used knock-in (KI) transgenic mice harbouring the FHM-1 mutation R192Q to study the consequences of this mutation in neurotransmission at the giant synapse of the auditory system formed by the presynaptic calyx of Held terminal and the postsynaptic neurons of the Medial Nucleus of the Trapezoid Body (MNTB). Although synaptic transmission seems unaffected by low frequency stimulation in physiological Ca2+ concentration, we observed that with low Ca2+concentrations (< 1 mM) excitatory postsynaptic currents (EPSCs) showed increased amplitudes in R192Q KI mice compared to WT, meaning significant differences in the non-linear calcium-dependence of nerve-evoked transmitter release. In addition, when EPSCs were evoked by broadened presynaptic action potentials (achieved by inhibition of K+channels) via Cav2.1 triggered exocytosis, the R192Q KI mice exhibited further enhancement of EPSC amplitude and charge compared with WT mice. Repetitive stimulation of afferent axons to the MNTB at different frequencies caused short term depression of EPSCs that recovered significantly faster in R192Q KI than in WT mice. Faster recovery in R192Q KI mice was prevented by the calcium chelator EGTA-AM, pointing to enlarged residual calcium as a key factor in accelerating the replenishment of synaptic vesicles.